BEHAVIOUR MANAGERS IN EARNING MANAGEMENT PRACTICES - Silmi Silmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to analyze the parties who experience losses due to the activities of managers in earnings management practices and to analyze actions or strategies that can be taken by company owners to reduce earnings management practices carried out by company managers. This study reviews the results of several relevant previous articles. The result of this study found that the company’s annual report which is opportunistic from earnings management practices carried out by manager result in losses for shareholders, corporate clients and stakeholders related to the company’s annual report. Strategies that can be carried out by company owners to reduce earnings management practices carried out by company managers, (1) By changing the accounting recording methods used by companies with lower risk methods in earnings management activities that can be carried out by company managers. (2) Implementing good corporate governance within the company, with the existence of good corporate governance will certainly reduce or limit the space for managers to practice earnings management.